PERANAN MOESLIM ROESLI DALAM PERKEMBANGAN PERS DI RIAU TAHUN 1954 – 1975 - Hartono, Tri; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Press is a vehicle for mass communication that carries out journalistic activities including searching, obtaining, storing, processing and conveying information in the form of writing, voice, images, data and graphics as well as other forms using print and electronic media. The purpose of this research was to find out the biography of Moeslim Roesli, knowing the role of Moeslim Roesli in the development of the press in Riau, knowing the obstacles faced by Moeslim Roesli in the development of press in Riau, and to find out the success and achievements of Moeslim Roesli in the journalism world. The method used in this research is the historical method. Data collection techniques are interview techniques, documentation, and literature studies, with research locations in the city of Pekanbaru. The results of the research explained that Moeslim Roesli was a figure of journalist who had a lot of roles and contributed to the development of the press in Riau. Starting from his participation in establishing the Pewarta Kita newspaper in Bagan Siapi-api (1954), the figure behind the establishment of the National News Agency Institution Between Riau bureaus (1960), one of the founding figures of the Riau Indonesian Journalists Association (1963), succeeded in fighting for a set of newspaper printing machines first for Riau (1963), increasing the status of the Riau PWI with the status of Representative to Branch (1966). Moeslim Roesli also made many achievements in the journalistic competition in Riau.Key Words: Press, Role, Reporter, Riau